2017
DOI: 10.1186/s41110-017-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

High C-reactive protein instead of metabolic syndrome is associated with lower bioimpedance phase angle in individuals clinically screened for a lifestyle modification program

Abstract: Background: Phase angle (PhA) value is a useful tool for identifying cell membrane integrity dysfunction. It is known that metabolic syndrome (MetS) increases oxidative stress and inflammation; and consequently can promote cellular damage. We hypothesized that MetS and inflammatory blood markers could be associated with lower PhA values. Therefore, the aim of this study was to identify the association of PhA values with MetS and blood markers in individuals clinically screened for a lifestyle modification prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Similar to BP, we observed conflicting associations between raw bioelectrical impedance variables and blood lipids, as has been shown in previous studies (36,37). Under normal circumstances, HDL aids in maintaining the cell membrane through the prevention of cellular cholesterol toxicity (38), which occurs via HDL-mediated cholesterol efflux and inhibition of LDL oxidation (39).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to BP, we observed conflicting associations between raw bioelectrical impedance variables and blood lipids, as has been shown in previous studies (36,37). Under normal circumstances, HDL aids in maintaining the cell membrane through the prevention of cellular cholesterol toxicity (38), which occurs via HDL-mediated cholesterol efflux and inhibition of LDL oxidation (39).…”
Section: Discussionsupporting
confidence: 80%
“…A Spanish study showed that low tertile of phase angle is a cardiovascular risk factor in obese patients [ 27 ]. Controversially, in our study, 50 kHz whole-body phase angle had a positive correlation with ALT, AST, ALP, and TG, as supported by a study done by Moreto et al It can be deduced that 50 kHz whole-body angle is an indicator of good nutritional status in a healthy population and is not a good predictor of MetS [ 28 ].…”
Section: Discussionsupporting
confidence: 75%
“…As such, the use of PhA cut-offs values in this context are discouraged. Other studies confirmed negligible to moderate negative associations between PhA and CRP in adults, mostly with excess body weight [ 85 , 86 ]. These negative associations of similar strength between PhA and CRP were also found in clinical populations, including peritoneal dialysis [ 75 , 77 ], hospitalized patients (54.8% with malnutrition, and 34% with cancer) [ 39 ], psoriasis [ 81 ], Prader-Willi Syndrome [ 82 ], and COVID-19 [ 54 ].…”
Section: Phase Angle Inflammation and Cellular Damagementioning
confidence: 74%
“…Overall, PhA was associated with several direct inflammatory markers, such as CRP, TNF-α, IL-6, interleukin 1-β (IL-1β), interleukin-10 (IL-10), and indirect markers (i.e., malnutrition-inflammation score). Studies included patients with: chronic kidney disease [ 74 79 ], hospitalized [ 39 ], primary care [ 80 ], psoriasis [ 81 ], Prader–Willi Syndrome [ 82 ], COVID-19 [ 54 ]; additionally, studies also included older women [ 83 , 84 ], women with obesity [ 85 ], general population [ 86 , 87 ], and professional soccer players [ 88 ].…”
Section: Phase Angle Inflammation and Cellular Damagementioning
confidence: 99%